Development of SME Entrepreneurship in the Creative Economic Sector: The Influence of Innovation Management, Technology, and Motivation on Performance Improvement Factors in Indonesia - Indah Datin Nadliroh; Sudarmiatin Sudarmiatin; Ludi Wishnu Perdana (Jurnal Bisnis dan Manajemen, 2023)
This research aims to determine the influence of innovation management, technology, and motivation on SME business growth in the creative economy sector in Gresik, Indonesia. Quantitative methods were used to distribute questionnaires using purposive sampling techniques to 110 SMEs that produce and sell goods directly to customers. Data was processed using WarpPLS 8.0. The results of this research, innovation management, technology, and motivation have a significant effect on improving SME performance. Many indicators describing information technology were used to measure technology problems in this research. Practical implications to improve future performance, both governments and employers must increase technology training. Especially in Indonesia, entrepreneurship, for example, can be an inspiration for creative industries to use technology, innovate and encourage motivation to improve their business results.